Perfil eletroforético das proteínas séricas de frangos de corte alimentados com dietas contendo aflatoxinas e/ou argila clinoptilolita natural - Maciel, Roberto Marinho (2006)
Aflatoxins are metabolites from fungi, that may be injurious to animal health, resulting in reduced production and affecting poultry industry by decrease the growth rate and worsening feed conversion. A study was carried out to evaluate the electrophoresis profile of serum protein in broilers fed with diets containing aflatoxins and natural clinoptilolite clay. A total of 528 male broilers Ross were used, distributed in 6 treatments with 4 replications each: T1 control (without aflatoxins or clinoptilolite), T2 5ppm of aflatoxins, T3 0.25% of clinoptilolite, T4 5ppm of aflatoxins and 0.25% of clinoptilolite, T5 0.5% of clinoptilolite and T6 5ppm of aflatoxins and 0.5% of clinoptilolite. The broilers were placed in 24 boxes and submitted to treatments from 1 to 42 days, when they were slaughtered. Were analyzed the total proteins, albumin fractions, alpha 1, alpha 2, beta and gamma. The aflatoxins decreased (P<0.05) total protein, albumin, and globulins (alpha and beta fractions). However, no effect (P<0.05) of aflatoxins was observed about gamma fraction. The clinoptilolite no modify (P<0.05) the serum proteins. Related to control, broilers fed with diets containing aflatoxins and clinoptilolite presented low (P<0.05) levels of total protein, albumin, and globulins (alpha and beta fractions). In conclusion, aflatoxins change the electrophoresis profile and clinoptilolite is not able to protect against this change